The role of allogeneic hematopoietic stem cell transplantation in the treatment of solid tumors - Deptała, Andrzej; Asendrych, Alicja (Contemporary Oncology/Współczesna Onkologia, 2006)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) has become an established therapeutic approach for many hematological malignancies. Early attempts in transplantation usually used the myeloablative methodology. The myeloablative methodology means complete destruction of recipient bone marrow (including eradication of malignant cells) by the conditioning consisting of megachemotherapy and total body irradiation (TBI). This transplantation strategy has been called classic allo-HSCT. Animal studies performed in the eighties of the 20-th century revealed that myeloablation is not essential for the engraftment, and the conditioning containing immunosuppressive chemotherapy allows the stem cells to create their own marrow space through immunologic reactions, which lead to the reconstitution of hematopoiesis. Thus, non-myeloablative technology has been developed, and now is known as non-myeloablative stem cell transplantation (NST) or transplantation with reduced intensity conditioning (RIC). Clinical benefits and therapeutic successes of NST/RIC in hematological malignancies put certain researchers into the special concern of application of this procedure for the therapy of particular solid tumors. If allo-HSCT plays any role in the treatment of solid tumors, what are the indications for this therapy, and what are the limitations of the procedure, and who will benefit from such treatment. Followed by evidence-based medicine, the authors of the article have provided a comprehensive overview in answering these questions.